Smart Classroom Monitoring Using Novel Real-Time Facial Expression Recognition System - Shariqa Fakhar; Junaid Baber; Sibghat Ullah Bazai; Shah Marjan; Michal Jasinski; Elzbieta Jasinska; Muhammad Umar Chaudhry; Zbigniew Leonowicz; Shumaila Hussain (Applied Sciences, 2022)
Emotions play a vital role in education. Technological advancement in computer vision using deep learning models has improved automatic emotion recognition. In this study, a real-time automatic emotion recognition system is developed incorporating novel salient facial features for classroom assessment using a deep learning model. The proposed novel facial features for each emotion are initially detected using HOG for face recognition, and automatic emotion recognition is then performed by training a convolutional neural network (CNN) that takes real-time input from a camera deployed in the classroom. The proposed emotion recognition system will analyze the facial expressions of each student during learning. The selected emotional states are happiness, sadness, and fear along with the cognitive–emotional states of satisfaction, dissatisfaction, and concentration. The selected emotional states are tested against selected variables gender, department, lecture time, seating positions, and the difficulty of a subject. The proposed system contributes to improve classroom learning.